UPAYA MENINGKATKAN SERVIS BAWAH BOLA VOLI DENGAN MEDIA BOLA PLASTIK - Yusuf, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:The problem often faced by teachers during the learning is a service under the ball which students experienced difficulties in the learning objectives of this research is to improve the ability to serve the ball with a ball the plastic that is light on class V sdn 26 sui snapper district Kuburaya Form of research used is classroom action research (PTK). In a classroom action research (PTK) This is the subject of this study were teachers collaborate with fifth grade students of State Elementary School 26 sui snapper district Kuburaya totaling 26 students Based on the results of research carried out research have a positive impact on students because it consists of the first cycle and the second cycle of planning, implementation, observation and reflection. Learning first cycle of students who have recently graduated a total of 20 students or 77,% while students who have not passed amounted to 6 students, or 33%, then proceed to the second cycle so that students have the opportunity to repair the service under then ciba with plastic balls gradually so new to say pass 100% or 26 students who did not pass 0%. Keywords: Under Servis, Volleyball, Media